Tuning the mechanical properties of self-assembled mixed-peptide tubes - Sedman, V.L.; Chen, X.; Allen, S.; Roberts, C.J.; Korolkov, V.V.; Tendler, S.J.B. (Wiley, 2013)
In this study, nano- and microscale fibrillar and tubular structures formed by mixing two aromatic peptides known to self-assemble separately, (diphenylalanine and di-D-2-napthylalanine) have been investigated. The morphology, mechanical strength and thermal stability of the tubular structures formed have been studied. The tubes are shown to consist of both peptides with some degree of nanoscale phase separation. The ability of the mixed peptides to form structures, which display variable mechanical properties dependent on the percentage composition of the peptides is presented. Such materials with tuneable properties will be required for a range of applications in nanotechnology and biotechnology.